Some Remarks about the Subsidiary Role of Values in Max Weber’s Approach - Godek-Ostrouch, Lidia (Sensus Historiae, 2024)
In this paper, I am trying to understand the ole of values in the scientific work presented in the methodological writings of Max Weber. The assessment of the role of values and the consistency of Weber’s views on this matter is not as straightforward as it is commonly assumed. I will focus mainly on Weber’s category of value interpretation [Wertinterpretation]. In doing so, I justify and indicate several levels at which the role of values can be illustrated, and finally argue that Weber allows for—although to a limited extent—a certain methodological role of values in the scientific process.